COVID-19 and Long-Term Care Policy for Older People in Hong Kong. Issue 4 (3rd July 2020) - Lum, Terry; Shi, Cheng; Wong, Gloria; Wong, Kayla
ABSTRACT: Hong Kong is a major international travel hub and a densely populated city geographically adjacent to Mainland China. Despite these risk factors, it has managed to contain the COVID-19 epidemic without a total lockdown of the city. Three months on since the outbreak, the city reported slightly more than 1, 000 infected people, only four deaths and no infection in residential care homes or adult day care centers. Public health intervention and population behavioral change were credited as reasons for this success. Hong Kong's public health intervention was developed from the lessons learned during the SARS epidemic in 2003 that killed 299 people, including 57 residential care residents. This perspective summarizes Hong Kong's responses to the COVID-19 virus, with a specific focus on how the long-term care system contained the spread of COVID-19 into residential care homes and home and community-based services.